2021
DOI: 10.15252/emmm.202013076
|View full text |Cite
|
Sign up to set email alerts
|

SGK1 inhibition in glia ameliorates pathologies and symptoms in Parkinson disease animal models

Abstract: Astrocytes and microglia are brain‐resident glia that can establish harmful inflammatory environments in disease contexts and thereby contribute to the progression of neuronal loss in neurodegenerative disorders. Correcting the diseased properties of glia is therefore an appealing strategy for treating brain diseases. Previous studies have shown that serum/ glucocorticoid related kinase 1 (SGK1) is upregulated in the brains of patients with various neurodegenerative disorders, suggesting its involvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 131 publications
(160 reference statements)
1
33
0
Order By: Relevance
“…It has recently been shown that astrocyte and microglia senescence in PD can be mitigated by senolytic treatment with the serum and glucocorticoid related kinase 1 (SGK1) inhibitor GSK-650394 ( Kwon et al, 2021 ). NF-kB transcription factors are responsible for transcribing pro-inflammatory genes, including those for cytokines and chemokines ( Liu et al, 2017 ).…”
Section: Senolytics As a Therapeutic Avenue For Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that astrocyte and microglia senescence in PD can be mitigated by senolytic treatment with the serum and glucocorticoid related kinase 1 (SGK1) inhibitor GSK-650394 ( Kwon et al, 2021 ). NF-kB transcription factors are responsible for transcribing pro-inflammatory genes, including those for cytokines and chemokines ( Liu et al, 2017 ).…”
Section: Senolytics As a Therapeutic Avenue For Parkinson’s Diseasementioning
confidence: 99%
“…Through phosphorylation, SGK1 activates NF-kB pathways and promotes inflammatory responses ( Lang and Voelkl, 2013 ). GSK-650394 reduces cytokine levels and SGK1 overexpression boosted cytokine levels in cultured mice astrocytes and microglia from the cortex and ventral midbrain ( Kwon et al, 2021 ). Furthermore, Nurr1 and Foxa2 downregulate Sgk1 in the mouse cultured glia, as shown in microarray and RNA-seq data ( Kwon et al, 2021 ).…”
Section: Senolytics As a Therapeutic Avenue For Parkinson’s Diseasementioning
confidence: 99%
“…The role of obvious apoptosis-related transcripts like Casp9 (caspase 9) in neurodegeneration is well documented [59]. Enhanced transcription of Sgk1 (Serum/Glucocorticoid Related Kinase 1) is upregulated in the brains of PD patients [60]. Another upregulated transcript is Sparc (Secreted Protein Acidic and Cysteine-Rich) which has been reported to be expressed diff erently in Parkinson's LRRK2-derived astrocytes from iPSC [61].…”
Section: Glial Activation and Neuroin Lammationmentioning
confidence: 99%
“…Hence, UA may be considered a potential therapeutic drug for neurological diseases [88]. PD is a chronic progressive neurodegenerative disease described by motor and nonmotor features [127][128][129][130]. Its increasing degenerative effects on muscle regulation and mobility have a key clinical result for caregivers, families and patients [131].…”
Section: Neuroprotective Effect Of Uamentioning
confidence: 99%